High ratio of epi-25-(OH)-vitamin D3 to 25-(OH)-vitamin D3 increases the risk of asthma attack in American asthma adults: a population study - Biao Peng; Yi Xiong; Ting Ouyang; Qing He; Shuo Qi; ZhiChao Yang; Ling He; Da Liu (BMC, 2024)
Abstract Objective The relationship between vitamin D3 and asthma remains controversial. However, previous studies have largely overlooked the impact of epi-25-(OH)-vitamin D3. This study aims to investigate the effects of different forms of vitamin D3 on asthma attack in adults. Methods In this cross-sectional study, a total of 3,873 eligible adult participants were extracted from the national health and nutrition examination survey (NHANES) database from 2007 to 2018. Based on quartiles method, different levels of vitamin D were divided into four groups (Quartile 1-4). Bivariate correlation analysis was performed for vitamin D and covariates to avoid multicollinearity. Multivariate logistic regression was used to investigate the association between serum levels of vitamin D3 (epi-25-(OH)-vitamin D3 and 25-(OH)-vitamin D3) and asthma attack, adjusting for covariates including age, gender, race, length of time in the U.S., house poverty income ratio (PIR), education level, smoking history, hypertension history, and diabetes history. The ratio of epi-25-(OH)-vitamin D3 to 25-(OH)-vitamin D3 was used for secondary analysis of its association with asthma attack. The outcomes were assessed by odds ratios (ORs) and 95% confidence intervals (CIs). Results Among the 3,873 eligible adults American with asthma, 1,508 (38.94%) had experienced at least one acute asthma attack in the past year. There was no significant correlation between vitamin D and covariates. After adjusting for covariates including age, gender, race, length of time in the U.S., house poverty income ratio (PIR), education level, smoking history, hypertension history and diabetes history, we found a positive correlation between the ratio of epi-25-(OH)-vitamin D3 to 25-(OH)-vitamin D3 and asthma attack. Additionally, a high ratio of epi-25-(OH)-vitamin D3 to 25-(OH)-vitamin D3 was more common among elder, male, of normal weight, non-Hispanic American, have a long time stay in the U.S., a high house PIR, and a history of hypertension individuals. Conclusion Our findings suggest that attention should be given to asthma attack associated with a high ratio of epi-25-(OH)-vitamin D3 to 25-(OH)-vitamin D3 in American adults who are elderly, male, of normal weight, non-Hispanic Americans, have long-term residence in the U.S., a high house PIR, and a history of hypertension.